Pasantía en la construcción de un Muro Mecánicamente Estabilizado con la empresa Consorcio Obras de Mitigación 2019 (2021)
The 2019 Mitigation Works Consortium company carries out environmental and risk mitigation projects in relation to slope stabilization works in conjunction with the district institute for risk management and climate change (IDIGER), where it was proposed to carry out the intervention of the property called a high-risk area located in the neighborhood of el peñón the cortijo III sector. The project consists of intervening in the rocky massif, implementing a mechanically stabilized wall system with a geosynthetic reinforcement system. Through the execution of the project, organizational problems were evidenced in relation to control and monitoring of previous activities on site, for this reason the support of the student is required to assume the position of engineering assistant, performing tasks that strengthen the organization and control of the activities allowing to reinforce knowledge in the development of the project.